PGRN as an emerging regulator of lipid metabolism in neurodegenerative diseases - Yiyue Shi; Wenyu Hou; Bei Li; Caihong Zhu (Communications Biology)
Abstract Dysregulated lipid metabolism in microglia represents a hallmark of neuroinflammation and is often observed in a variety of neurodegenerative diseases. The exact molecular mechanisms underlying the induction of altered lipid homeostasis and how it contributes to neurodegeneration remain to be deciphered. Progranulin (PGRN) is a lysosomal glycoprotein encoded by GRN. Loss-of-function mutations or variants of GRN have been linked to various neurodegenerative diseases. PGRN has recently been identified as a regulator of lipid droplet formation in microglia. Additionally, PGRN has been reported to interact with various molecules to modulate lysosomal lipid metabolism, including glycerolipids and sphingolipids in neurons. Hence, PGRN deficiency-mediated lipid dysregulation may represent a significant contributing factor to the neuroinflammation and the pathogenesis of related neurodegenerative diseases. Understanding how PGRN regulates lipid metabolism is crucial for developing therapeutic strategies to restore lipid homeostasis in microglia and mitigate neuroinflammation, thus offering hope for effective treatments to combat these neurodegenerative disorders in the future.